Is broad-scale smoke–water application always a useful tool for improving seedling emergence in post-mining restoration? Evidence from jarrah forest restoration in Western Australia - Daws, M.; Downes, Katherine; Koch, J.; Willyams, D. (Elsevier, 2014)
It has been widely advocated that smoke–water application to topsoil can substantially improve restoration success by enhancing seed germination. This is despite few studies having tested the effects of smoke–water on seedling emergence in field-scale restoration trials. Here we report the effects of applying a commercially available smoke solution (Regen 2000®), at rates between 0 and 100 mL m- 2, on jarrah forest sites being restored after bauxite mining in the southwest of Western Australia. Smoke solutions stimulated the seed germination of a range of species in laboratory experiments. In addition, smoke–water stimulated germination of Stylidium affine seeds sown directly into the first field experiment. However, apart from the effect on sown S. affine seeds, smoke–water application had no effect on subsequent seedling numbers, species richness or the relative proportion of seedlings in different growth-form categories in either of the two field experiments. These findings suggest that smoke–water application does not always ensure enhanced restoration outcomes.